Is the Cascading Training Model Effective for Continuous Professional Development? A Review of Teachers’ Experiences - Hugh John, Leong; Soubakeavathi, Rethinasamy (2021)
Continuous professional development (CPD) plays an integral role in educational reform and in the development and enhancement of teachers’ pedagogical skills and knowledge. In Malaysia, the cascade training model is often preferred for CPD programmes in public secondary schools. This may be due to cost effectiveness and reach, where many teachers can be trained in a short timeframe. Critics of the cascade model of training tend however, point to a risk of knowledge being diluted as it is transferred from the trainers to the attendees and then to teachers in schools. This paper focuses on documenting the experiences of Malaysian secondary school English teachers attending school-based assessment (SBA) CPD training courses using the cascade training model. Data was collected from 16 English teachers from 16 public secondary schools through in-depth semi-structured interviews. The findings indicate that there were mixed experiences of teachers attending cascade training programs and that of subsequent trainings that were conducted by attendees of the programmes. These experiences were affected largely by the quality of the training programme (i.e. design of program curriculum and materials), trainer quality, participants selected, and follow up support afforded to participants. This paper will culminate with recommendations for further CPD improvements.